Modelling and simulation of a biomass-based integrated gasification combined cycle with carbon capture: comparison between monoethanolamine and potassium carbonate. Issue 1 (March 2020) - Ghiat, Ikhlas; AlNouss, Ahmed; Mckay, Gordon; Al-Ansari, Tareq
Abstract: There are global efforts to reduce the impacts from climate change by limiting increases in temperature to 1.5 °C until 2030, and achieve carbon neutrality by 2050. Thus, it is necessary to design new neutral processes and systems that can meet the varying and growing demands of the population in terms of energy, water and food. One of the main carbon emitters and contributors to climate change is the energy industry, which primarily uses oil and natural gas as an energy source. Fortunately, alternative resources are available such as renewable energies that assemble various environmental and economic benefits. However, more work is necessitated to efficiently utilise these resources by designing, analysing, and optimising existing and new renewable energy-based processes. Therefore, this study proposes a net negative carbon emissions energy system that utilises waste biomass as a feedstock. A biomass based integrated gasification combined cycle combined with a post combustion carbon capture unit by means of chemical absorption is designed and analysed. Two different chemical solvents are used for comparison: Monoethanolamine (MEA) and potassium carbonate. The proposed integrated system is modelled and simulated in Aspen Plus software, and is analysed thermodynamically in terms of energy and exergy efficiencies. A sensitivity analysis is also conducted to assess the effect of varying operating conditions such as flowrate, and temperature of the lean solvent, and the pressure inside the stripper. At design conditions with 80% carbon capture, the system generates 419 kW of electricity and operates at -0.32 kg/kWh of CO2 for both the potassium carbonate and MEA systems.